An Analysis Of Students’ Responses To English Teaching Material In Google Classroom And Whatsap At SMAN Muko-Muko - Destia Eka Krisdayanti; M. Khairi Ihsan; Hevriani Sevrika (STKIP PGRI Sumatera Barat, 2023)
This research was motivated by student responses to English teaching materials in Google Classroom and Whatsapp at SMAN 07 Muko-Muko for the academic year 2021/2022. This research is a qualitative research with a descriptive method that aims to analyze and see the types of responses when given English teaching materials through the Google Classroom and Whatsapp applications. The total sample in this study was 71 students from 4 classes. Data were collected by researchers by distributing questionnaires to students directly with a total of 20 statements related to student responses to English teaching materials. There are three types of response types, namely cognitive, affective, and conative responses. The results of this study indicate that the dominant students have an Affective response to English teaching materials in Google Classroom and Whatsapp as a medium in learning. However, of all the types of responses given by students, Affective responses were the most common type found to students.Keywords: Types of Responses, Teaching Materials, Google Classroom, WhatsApp.